Application of Biologics in the Treatment of Asthma in the Past Two Decades: A Bibliometric Analysis and Beyond - Zhou Z; Chen X; Liang S; Li J; Zhong N; Chen R (Journal of Asthma and Allergy)
Zicong Zhou,1,* Xiaoying Chen,1,* Shixiu Liang,1 Jing Li,1 Nanshan Zhong,1,2 Ruchong Chen1,2 1State Key Laboratory of Respiratory Disease, Joint International Research Laboratory of Respiratory Health, National Clinical Research Center for Respiratory Disease, National Center for Respiratory Medicine, Department of Allergy and Clinical Immunology, Guangzhou Institute of Respiratory Health, the First Affiliated Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Guangzhou National Lab, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruchong Chen, Email chen_rch@163.com Nanshan Zhong, Email nanshan@vip.163.comAbstract: This study aims to demonstrate the bibliometric characteristics of articles on biologics for asthma treatment over the past two decades. There were 3395 articles published in 653 journals from 91 countries/regions from January 1, 2000 to September 30, 2023. The results showed biologics changes the course of asthma has attracted the interest of researchers and asthma remission has recently been proposed by researchers. Therefore, the goal of T2-high asthma management was shifted from controlling to complete remission. There was also growing interest among researchers in alleviating symptoms in T2-low asthma. New biological targets also need to be discovered when patients do not achieve satisfactory therapeutic outcomes with biologic agent, and one of the potential future direction for a treatment breakthrough lies in the combination of two biologics or the utilization of novel biologics that target dual sites. The development of biologics has progressed rapidly and has demonstrated their effectiveness in clinic, however, biologics still face multifaceted challenges and require further research to identify additional targets or enhance efficacy.Keywords: biologics, asthma, T2 inflammation, bibliometric analysis